STRATEGIC OPTIONS AND PARAMETERS OF FACILITATION OF THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN THE CONDITIONS OF EUROPEAN INTEGRATION - POLKOV, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the role of strategic alternatives to facilitation as a key conceptual tool that provides agricultural enterprises with the opportunity to choose the most effective development trajectories in the context of European integration transformations. It is proven that these alternatives contribute to the flexibility of management decisions, taking into account the characteristics of the external environment, internal resource potential and the level of institutional maturity of enterprises. It is determined that facilitation, going beyond the limits of operational interaction, acquires a strategic nature and becomes an important mechanism for supporting the sustainable development of the agricultural sector. It is noted that the goals of facilitation set the content, direction and expected results of interaction between participants, serving as a guide for choosing appropriate methods, formats and the degree of involvement. It is emphasized that a clear formulation of goals transforms facilitation into a strategic management tool that not only ensures adaptation to changes, but also actively contributes to the formation of new, innovative models of enterprise development. It is proposed to take into account the type of enterprise, in particular the scale, degree of innovation, level of institutional integration or vulnerability in crisis conditions, when agreeing on target settings, which allows avoiding unified approaches and ensuring targeted, targeted facilitation influence. It is determined that each target setting requires the use of an adequate facilitation model, the choice of which should be based on the content of the setting, the willingness of participants to cooperate and the desired level of transformation. Such an approach guarantees the methodological consistency of the facilitation process and increases its effectiveness. It is emphasized that in the conditions of European integration, facilitation ceases to be a purely auxiliary tool and acquires the status of a key mechanism for adaptation and development, which is of strategic importance for the formation of a new management culture in the agricultural sector, focused on partnership, transparency and sustainability. The generalization of strategic alternatives and target settings of facilitation allowed us to identify the conceptual framework of managerial influence on the development of agricultural enterprises. At the same time, it is noted that the effectiveness of facilitation strategies depends not only on the correct choice of models and goals, but also on the ability to mobilize internal and external resources necessary for their implementation, which is an important area of further research and practical implementation.